2006
DOI: 10.1111/j.1467-7652.2006.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐free transgenic (MFT) near‐isogenic introgression lines (NIILs) of ‘golden’ indica rice (cv. IR64) with accumulation of provitamin A in the endosperm tissue

Abstract: SummaryWe have developed near-isogenic introgression lines (NIILs) of an elite indica rice cultivar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The products of the primary, secondary and tertiary reactions were analysed on a 1.5% agarose gel. Fragments exhibiting a difference in size consistent with nested gene‐specific primer positions were cloned using pGEMT‐easy vector (Promega, Madison, WI) and sequenced as described earlier (Baisakh et al. , 2006b).…”
Section: Methodsmentioning
confidence: 99%
“…The products of the primary, secondary and tertiary reactions were analysed on a 1.5% agarose gel. Fragments exhibiting a difference in size consistent with nested gene‐specific primer positions were cloned using pGEMT‐easy vector (Promega, Madison, WI) and sequenced as described earlier (Baisakh et al. , 2006b).…”
Section: Methodsmentioning
confidence: 99%
“…The proof of concept has been demonstrated that genes psy and crtI or psy, crtI and lycopene b-cyclase under endosperm-specific promoters have been effective for elevating b-carotene concentration in transgenic rice, with more b-carotene in polished grains. More importantly, the incorporation of genes for carotenogenesis in seeds by transgenesis or by introgression did not change any significant agronomic characteristics in rice plants (Paine et al 2005;Baisakh et al 2006;Datta et al 2006Datta et al , 2007.…”
Section: Enhancing Seed Iron Zinc and B-carotene Using Transgementioning
confidence: 99%
“…The differences between the introgression lines in a subcluster were negligible and would be further minimized in the next BC generation. This suggested that the introgression of the two genes (psy and crtI) capable of installing the entire carotenogenic pathway only resulted in minor genome changes in IR64 (Baisakh et al 2006). Introgressed IR64 from original japonica rice (T309) also showed lower carotenoid levels (Baisakh et al 2006; Table 1).…”
Section: Phenotypic Characters Of the F1s And Backcross Progeniesmentioning
confidence: 88%
“…This suggested that the introgression of the two genes (psy and crtI) capable of installing the entire carotenogenic pathway only resulted in minor genome changes in IR64 (Baisakh et al 2006). Introgressed IR64 from original japonica rice (T309) also showed lower carotenoid levels (Baisakh et al 2006; Table 1). Efforts have been made to select a transgenic event with a simple and low-copy transgene for a Mendelian 3:1 segregation pattern and eventually to develop homozygous lines with acceptable agronomic performance.…”
Section: Phenotypic Characters Of the F1s And Backcross Progeniesmentioning
confidence: 88%
See 1 more Smart Citation